2013
DOI: 10.1155/2013/972863
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Effect of Fuzheng Huayu Recipe on Fibrotic Liver in Rats

Abstract: Hepatic fibrosis is a common pathological process of chronic liver diseases and would lead to cirrhosis, and Fuzheng Huayu (FZHY) is an effective Chinese herbal product against liver fibrosis. This study observes FZHY influence on proteome of fibrotic liver with differential proteomic approach and aims to understand FZHY multiple action mechanisms on liver fibrosis. The liver fibrosis models were induced with intraperitoneal injection of dimethylnitrosamine for 4 weeks in rats and divided into model control (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The biological role of AKR1 levels in diabetic glomerular fibrosis is unclear. Previous study clearly demonstrated that the fibrotic liver had the decreased expression levels of AKR1 when compared to the normal liver 32 indicating that AKR1 responsible for fibrogenesis in liver. Interesting, AKR1 was up-regulated in association with serum AFP, and was an independent risk factor for HCC in chronic hepatitis C patients, suggesting its possible involvement at a very early stage of hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 94%
“…The biological role of AKR1 levels in diabetic glomerular fibrosis is unclear. Previous study clearly demonstrated that the fibrotic liver had the decreased expression levels of AKR1 when compared to the normal liver 32 indicating that AKR1 responsible for fibrogenesis in liver. Interesting, AKR1 was up-regulated in association with serum AFP, and was an independent risk factor for HCC in chronic hepatitis C patients, suggesting its possible involvement at a very early stage of hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 94%
“…Fu-zheng-hua-yu (FZHY) is an effective Chinese herbal product that can cure liver fibrosis. A study using 2-DE coupled with MALDI-TOF-MS showed that FZHY regulated the expression of aldehyde dehydrogenase, gammaactin, fructose-bisphosphate aldolase B, aldo-keto reductase, S-adenosylhomocysteine hydrolase isoform, and HSP 90 in a dimethyl nitrosamineinduced rat model of liver fibrosis (37). The results indicate that the molecular mechanism by which FZHY affects liver fibrosis may be through the modulation of proteins involved in metabolism and stress responses, as well as myofibroblast activation.…”
Section: Liver Diseasesmentioning
confidence: 90%
“…For protein identification, the dried spots were analyzed using a REFLEX-III (Bruker) MALDI-TOF-MS 50 . The spectrometer was run in the positive ion mode and in the reflector mode with the following settings: pulsed N2 laser 337 nm, ion source 1 = 19.00 kV, ion source 2 = 16.50 kV, reflector voltage = 20.00 kV, lens voltage = 8.80 kV, pulsed ion extraction time = 80 ns, matrix suppression = 400 Da, and positive reflector mode.…”
Section: Methodsmentioning
confidence: 99%